Modeling the Factors of Intercity–Interprovincial Bus Accidents as a Basis for Formulating Road Transport Safety Improvement Strategies (Case Study: Bus Drivers at Jatijajar Type a Terminal) - Farah Sandi; Masrono Yugihartiman; Rossy Armyn Machfudiyanto (Green Publisher Indonesia, 2026)
The high frequency of traffic accidents in the land transportation sector, especially those involving intercity and interprovincial buses (AKAP), indicates that the safety aspect of passenger transportation is still a significant problem. This study aims to analyze the factors that contribute to the risk of accidents for AKAP bus drivers at the Jatijajar Type a Terminal, Depok. A quantitative approach is used with the Structural Equation Modeling (SEM) method to test the multidimensional relationship between driving behavior, drivers' mental and physical condition, company management, government regulations, environment and traffic, and vehicle factors to accident risk. The SEM-PLS analysis revealed that five factors significantly influenced the accident, collectively explaining 59.8% of the total variance in AKAP bus accidents. Mental and Physical Condition factors were the strongest predictors (coefficient = 0.302), followed by Risky Driving Behavior (0.273), Environment and Traffic (0.222), Company Management (-0.227), and Government Regulation (-0.194). Vehicle factors did not show a significant influence. Based on these findings, two priority strategies validated by experts were formulated: (1) Transformation of the driving profession through standardization of competencies and vocational education, and (2) Restructuring of wage and incentive systems to improve driver welfare and eliminate economic pressures that trigger risky behavior. This study provides a theoretical contribution by comprehensively modeling the factors of AKAP bus accidents and providing strategic recommendations that can be used as a reference for the government and bus operators in formulating more targeted policies to improve road transportation safety